Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
The coefficient of x is 6
Step-by-step explanation:
The two expressions are
(x)=-5x+1f(x)=−5x+1
and .
f(x)=6f(x)=6.
The sum of the two expressions is
f(x)=-5x+1f(x)=−5x+1(f(x)=6f(x)=6.)
When we group like terms the expression will be,
f(x)=-5x+1f(x)=−5x+1(f(x)=6f(x)=6.)=f(x)=-5x+1f(x)=−5x+1(f(x)=6f(x)=6.)
When we simplify the expression will now be
f−5x+1(f(x)=6.)
The coefficient of x is the constant behind x in the expression.
The coefficient of x is 3 therefore the answer is 3 .
Step-by-step explanation:
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.